CONTROVERSIAL AND UNRESOLVED TOPIC METHOD (CUT) TO IMPROVE THE STUDENTS’ SPEAKING ABILITY AT SECOND GRADE OF SMA MUHAMMADIYAH 7 MAKASSAR - Burhanuddin, Wildhan; Kadir, Husain (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
Controversial and Unresolved Topic Method (Cut) To Improve the Students’ Speaking Ability at Second   Grade of SMA Muhammadiyah 7 Makassar. The objective of the research will find out the improvement students’ speaking ability by Controversial and Unresolved Topic (CUT) Method at the second grade of SMA Muhammadiyah 7 Makassar. This research will use Classroom Action Research that consisted two cycles. The research population was the second grade of SMA Muhammadiyah 7 Makassar academic year 2013/2014. The sample of this research consisted of 24 students. The researcher will obtain the data by using speaking test and observation sheet. The reason why this research focuses on the controversial and unresolved topic method was that it will give the students motivation to study English special in English skill. Besides that this method will make the students become more confident to express their ideas, more friendship among others, and all the students can connect a good atmosphere.